MATERIALS TO COGNITION OF FAUNA OF THE WEEVILS OF THE GENUS SEUTORHYNCHUS (COLEOPTERA, CURCULIONIDAE) OF THE NORTH-EASTERN CAUCASUS - M. Sh. Ismailova; G. M. Mukhtarova (Юг России: экология, развитие)
As a result of studying fauna of beetles-weevils of family Ceutorhynchus of North-Eastern Caucasusare 68 speciesrevealed. Bioecological features of the species are presented, data of distribution and the analysis of the received materials are given.